Jewish Writers in Contemporary Germany: The Dead Author Speaks - Sander L. Gilman (Studies in 20th & 21st Century Literature, 1989)
The question I wish to address in this essay is really quite simple: Given the fact that there are "Jews" who seem to play a major role in contemporary German "Kultur" (at least that narrower definition of culture, meaning the production of cultural artifacts, such as books—a field which, at least for Englemann, was one of the certain indicators of a Jewish component in prewar German culture)—what happened to these "Jews" (or at least the category of the "Jewish writer") in postwar discussions of culture? Or more simply: who lulled the remaining Jews in contemporary German culture and why? Why is it not possible to speak about "German-Jews" in the contemporary criticism about German culture? And, more to the point, what is the impact of this denial on those who (quite often ambivalently) see (or have been forced to see) themselves as "Germans" and "Jews," but not as both simultaneously.
Keywords: Jews; German; Kultur; culture; artifacts; books; book; Englemann; Jewish; prewar German culture; prewar; Germany; Jewish writer; postwar; contemporary German; German-Jews; criticism; denial